[Beggars ; Putok ; Sto. Nino squatters ; Baclaran vendors ; Timbangan ; Airport taxis [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Tackles Igorot beggars from the Cordilleras who flock to Manila; laws in cottage industry that sets the issue on fire and ban on the manufactuer and sale of fireworks; the squatters on Meralco Ave. Sitio Sto. Nino Pasig City; the ambulant vendors in Baclaran; the cheating in the use of weighing scales in wet market; and the story of an airport taxi service accused of overcharging and discrimination against Filipinos.
Beggars (17 min.) -- Sto. Nino Squatters (10 min.) -- Baclaran vendors (8 min.) -- Timbangan (8 min.) -- Airport taxis (9 min.)
VHS.
Keywords: Beggars -- Philippines; Firecrackers -- Philippines -- Bulacan; Peddlers and peddling -- Philippines -- Baclaran; Squatters -- Philippines -- Pasig City; Vending stands -- Philippines -- Baclaran